[24]Crown-8-modified carbon nanotubes for templating metal deposition and active materials for pseudocapacitors. Issue 1 (11th November 2020) - Zhou, Ruitao; Tang, Fung-Kit; Sun, Raymond Wai-Yin; Tse, Man Kin; Chen, Yujie; Chan, Albert Sun Chi; Chen, Shengzhou; Zhu, Xunjin; Leung, Ken Cham-Fai
Abstract : A uniform nickel film could be coated on crown ether-modified carbon nanotubes (c-CNTs) by electroless deposition. Abstract : A uniform nickel film could be coated on crown ether-modified carbon nanotubes (c-CNTs) by electroless deposition. The products CNT@Ni and c-CNT@Ni were oxidized and compressed into CNT@Ni@(NiOH)2 and c-CNT@Ni@(NiOH)2 discs, respectively. The areal and volumetric capacitances of CNT@Ni@(NiOH)2 and c-CNT@Ni@(NiOH)2 were compared and c-CNT@Ni@(NiOH)2 showed a lower resistance.